NILAI-NILAI PENDIDIKAN MORAL DALAM PERSPEKTIF NOVEL HATI SUHITA KARYA KHILMA ANIS - PANGESTI, DILA AYU; MUBIN, NURUL (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Education is a conscious effort to realize active learning to develop the potential that exists in oneself with spiritual strength, self-control, skills and noble morals that are needed within oneself. Moral education can be interpreted as character education. Moral education is education of noble values ??that originate from religion, customs and national culture in the context of personal change towards a better person. Moral education never departs from the noble values ??in the moral values ??of the Indonesian nation whose aim is to form children in this country as children who have a sense of humanity, unity and uphold religious values. This research is a type of library research because the research source is taken from a novel. This research aims to explore the values ??of moral education in the novel Hati Suhita by Khilma Anis. The data collection technique uses documentary techniques by collecting writings that describe the values ??of moral education in the novel Hati Suhita. Then grouped according to the problem to be described. The primary data source used by researchers is the novel Hati Suhita by Khilma Anis and secondary data in the form of relevant books, articles and journals. The results of the analysis show that the novel Hati Suhita contains three main categories of moral values. The first moral value is religious moral values ??(religious morals) which include an attitude of gratitude, surrender, prayer, and praising God's majesty. The second moral value is a social moral value that regulates relationships between humans, such as mutual respect, mutual assistance and respect. The third moral value is personal moral values ??(individual morals) which are related to self-development, such as self-confidence, patience, determination, maintaining self-esteem, never giving up, daring to admit mistakes, and sincerity. ABSTRAKPendidikan merupakan usaha sadar untuk mewujudkan pembelajaran yang aktif mengembangkan potensi yang ada pada diri dengan kekuatan spiritual, pengendalian diri, keterampilan serta akhlak mulia yang diperlukan dalam diri. Pendidikan moral dapat disama artikan dengan pendidikan budi pekerti, Pendidikan moral merupakan Pendidikan nilai luhur yang bersumber dari agama, adat istiadat dan budaya bangsa dalam rangka perubahan pribadi menuju pribadi yang lebih baik. Pendidikan moral tidak pernah beranjak dari nilai-nilai luhur dalam tatanan nilai moral bangsa Indonesia yang tujuanya untuk membentuk anak di negeri ini sebagai anak yang memiliki rasa kemanusiaan persatuan menjunjung tinggi nilai religius. Penelitian ini termasuk jenis penelitian kepustakaan atau library research karena sumber penelitiannya diambil dari novel. Penelitian ini bertujuan untuk menggali nilai-nilai pendidikan moral dalam novel Hati Suhita karya Khilma Anis. Teknik pengumpulan data menggunakan teknik dokumentsi dengan mengumpulkan tulisan yang menggambarkan nilai-nilai Pendidikan moral dalam novel Hati Suhita. Kemudian dikelompokkan sesuai dengan permasalahan yang akan dideskripsikan. Sumber data primer yang digunakan oleh peneliti adalah novel Hati Suhita karya Khilma Anis dan data sekunder berupa buku-buku, artikel dan jurnal yang relevan. Hasil analisis menunjukkan bahwa novel Hati Suhita mengandung tiga kategori utama nilai moral. Nilai moral yang pertama adalah nilai moral agama (moral religi) yang meliputi sikap bersyukur, berserah diri, berdoa, dan memuji keagungan Tuhan. Nilai moral yang Kedua adalah nilai moral sosial yang mengatur hubungan antar manusia, seperti sikap saling menghargai, tolong-menolong, dan menghormati. Nilai moral yang Ketiga adalah nilai moral personal (moral individu) yang berkaitan dengan pengembangan diri, seperti percaya diri, sabar, teguh pendirian, menjaga harga diri, pantang menyerah, berani mengakui kesalahan, dan ikhlas.